Prácticas ambientales en el sector de la construcción: El caso de las empresas constructoras Espa\~nolas - P. Pi\~neiro García; A. García-Pintos Escuder (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2009)
There is plenty of literature analyzing the environmental management practices of firms, from a multisectorial perspective as well as a sectorial perspective. Nevertheless, very few studies have been carried out in the construction sector, probably because of the peculiarities of the industry and the subsequent singularities of the environmental management in building firms. In this context, this paper has a double aim: on one hand, to design a broad list of environmental management practices of building firms, and on the other hand to analyze the implantation level of these practices in the Spanish building firms.
Keywords: 330; environmental management; construction firms